(untitled) (University Heart Journal, 2011)
Coronary artery bypass grafting (CABG) is a well established treatment modality for coronary artery disease (CAD). However with the trend towards aggressive per cutaneous interventions (PCI) by the cardiologists, more and more patients with poor quality, diffusely diseased coronary arteries are coming for CABG. Quite often these arteries require endarterectomy to ensure revascularisation. Initial experience world wide with coronary endarterectomy was bad enough for many surgeons not advocating it. However recent papers have shown greatly improved results. This was a retrospective study of five hundred consecutive patients undergoing CABG between 19th August 2006 and 1st of July 2008 at Ibrahim Cardiac Hospital and Research Institute (ICHRI). Pre-operative and Intra-operative variables which could influence outcome were analysed. Of the total patients who had at least one endarterectomy done were labeled as Endarterectomy (EA) group, while patients without endarterectomy were labeled as Control group. Post operative outcome showed results comparable to CABG without endarterectomy can be achieved. We have described our selection criteria and surgical technique. Our protocol did not bring about a statistically significant increase in bypass time, cross clamp time. It also did not change the number of grafts per patient. Our experience shows coronary endarterectomy can be done in order to achieve full revascularisation with very safe and acceptable outcome. Key words: CABG; Coronary endarterectomy DOI: 10.3329/uhj.v6i2.7247 University Heart Journal Vol. 6, No. 2, July 2010 pp.70-73